Creditor rights, claims enforcement, and bond performance in mergers and acquisitions - Renneboog, Luc; Szilagyi, Peter G.; Vansteenkiste, Cara (Journal of International Business Studies, 2017)
This article shows that country-level differences in creditor protection affect bond performance around cross-border M&A announcements. Using Eurobonds and a global sample of 1,100 cross-border M&As, we find that the bondholders of bidding firms respond more positively to deals that expose their firm to a jurisdiction with stronger creditor rights and more efficient claims enforcement through courts. Positive creditor protection spillovers are enhanced by now-global jurisdictional cooperation in multinational insolvencies and creditors’ ability to do insolvency arbitrage. The spillover effects we observe are stronger for firms with higher asset risk, longer maturity bonds, and a higher likelihood of financial distress.